(3OjhGf LQjQs - (3LQjQ Hf YWjI Hf MPjaI GdNWaj GdjQHhYj GdJejej,J (B110 (3g` s
(3ChdgG (B:s
(3WQH GdaDGO dPcQgf hbO eVJ HGddjd CLfMI GdfLhe aeGdG s
(3BNQgG (B:s
(3jGGHf GdNHjKI Cjf ef CYOOJe dHfj aRGQI Ch dqMjri YGeQ s
(3fSNI NGeSI bWY efgGs
(3hQO CjVkG JMJ Qbe (B831(3, (B832(3, (B877(3, (B1020(3, (B1021(3, (B1022(3, (B2399s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B111s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B66 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B782s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs